Probabilistic Calculation of Tolerances of the Dimension Chain Based on the Floyd-warshall Algorithm; Procedia Engineering; Vol. 152 : 2nd International Conference on Industrial Engineering (ICIE-2016) - Mukholzoev A. V. Andrey Vladimirovich (2016, 2016)
Title screen